1997
DOI: 10.1080/713685866
|View full text |Cite
|
Sign up to set email alerts
|

Death, bereavement and college students: A descriptive Analysis

Abstract: The author presents two studies dealing with death and bereavement in the lives of college students. The first study, conducted with 994 undergraduates in an introductory course on human development, involved a survey about death and bereavement in their lives. The second study consisted of interviews with 18 undergraduates bereaved over the death of a family member or a friend. Interview topics included reminiscence, avoidance, emotions, expectations about recovery, and means used to cope. A finding with seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
65
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 10 publications
9
65
1
Order By: Relevance
“…Such changes could be related to a lack of knowledge about grief or a lack of skill in how best to interact with troubled peers. Research suggests that bereaved students do not perceive their peers as supportive (Balk, 1997;Silverman, 1987). In fact, bereaved students report that their peers are uncomfortable discussing the topic of grief (Balk, 1997) and generally turn away or communicate the need for the bereaved to "get over it" (Silverman, 1987, p. 393).…”
Section: Dual Process Model Of Coping and College Studentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Such changes could be related to a lack of knowledge about grief or a lack of skill in how best to interact with troubled peers. Research suggests that bereaved students do not perceive their peers as supportive (Balk, 1997;Silverman, 1987). In fact, bereaved students report that their peers are uncomfortable discussing the topic of grief (Balk, 1997) and generally turn away or communicate the need for the bereaved to "get over it" (Silverman, 1987, p. 393).…”
Section: Dual Process Model Of Coping and College Studentsmentioning
confidence: 99%
“…However, there is some empirical indication that the theory could apply to their experience. For example, Balk (1997) found that bereaved college students indicated the following practices to be helpful in their process of coping with their death loss: "remembering good things about the deceased, engaging in religious practices, crying, keeping busy, talking about the death, and thinking the person is better off because he/she is dead" (p. 215). It is interesting to note that these spontaneously offered strategies do seem to represent a balance of loss and restoration-oriented coping efforts.…”
Section: Dual Process Model Of Coping and College Studentsmentioning
confidence: 99%
See 3 more Smart Citations